2013
DOI: 10.1111/his.12191
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma of the jaw: an analysis of a series of 74 cases

Abstract: Osteosarcoma of the jaw was the most frequent primary malignant tumour of the jaw. Female gender and a predominantly chondroblastic pattern may be associated with a worse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 25 publications
3
48
0
Order By: Relevance
“…2,15,22 However, one study did find that females diagnosed with JOS may have a worse prognosis. 30 In addition, sex distribution of JOS is a controversial issue, with multiple studies finding that males are more commonly affected owing to a longer period of skeletal growth and additional volume of bone in males. 2,6,9 The data from our present study, to our knowledge the largest JOS study to date show that JOS occurs equally in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…2,15,22 However, one study did find that females diagnosed with JOS may have a worse prognosis. 30 In addition, sex distribution of JOS is a controversial issue, with multiple studies finding that males are more commonly affected owing to a longer period of skeletal growth and additional volume of bone in males. 2,6,9 The data from our present study, to our knowledge the largest JOS study to date show that JOS occurs equally in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Even though PMT also contains MNGCs, they are fewer in number and have fewer nuclei [66]. While a similarity between PMT and osteosarcoma is the production of bone, PMT is cytologically bland while osteosarcoma displays cytologic atypia and bone production is variable with many tumors producing some cartilage as well [67]. Folpe also mentioned that PMT comprised only 9 out of over 150,000 mesenchymal tumor consultations seen [61,68].…”
Section: Discussionmentioning
confidence: 99%
“…Mardinger et al-for example-reported the highest prevalence for chondroblastic OS (42%), osteoblastic osteosarcomas being lesser (33%) in JOS [37].…”
Section: Osteosarcoma -Biology Behavior and Mechanismsmentioning
confidence: 99%